IMPROVING STUDENTS’ SPEAKING SKILL THROUGH YOUTUBE VIDEO: SYSTEMATIC REVIEW - Mohammad Ulin Nuha; Saputri, Tiyas (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2021)
This study aims to describe youtube video as an effective medium to improve English speaking skills and to gather some information related to the use of YouTube videos in teaching and learning English. The approach used in this research was systematic analysis. This research used 10 sources that consisted 4 theses and 6 articles. Technique of data analysis used in this study was DescriptiveResearch.The data in this study are sentences. All sentences have been selected by researchers from several relevant journals and theses. Data collection is carried out by researchers by searching several journals or theses that have similarities in reading texts or research media. Data analysis using pre-test and post-test that has been investigated by researchers. The result of this study is using YouTube videos as an alternate since It can be seen from differences in the pre-test post-test results of students taken from various sources by using Youtube video. In reality, Youtube video media can not only be adapted to children but can also be extended to all level of educationas well as allowing students to quickly practice their own speaking skills.